2019
DOI: 10.20448/journal.522.2019.52.349.361
|View full text |Cite
|
Sign up to set email alerts
|

Which Country is More Effective in Science Teaching? Evidence from PISA 2015 as a Secondary School Assessment Tool

Abstract: The aim of this study is to determine how effectively different countries use educational inputs in the process of science education. The study is in the descriptive model and the data is derived from the PISA 2015 data set, which provides information to countries on secondary education programs. Data from 70 countries, including Turkey, were used in the study. The effectiveness of Turkey in the process of science teaching in secondary education has been compared with other countries and suggestions have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…On the teacher level, it has been demonstrated that teacher shortage is negatively connected with students’ scientific literacy performance in many countries, such as in Brazil ( Kalkan et al, 2020 ), in Turkey and Singapore ( Alatli, 2020 ), and in Finland ( Nissinen et al, 2018 ). By studying PISA 2015 data, Ilgaz et al (2019) extended this negative relation to 70 countries. Furthermore, teachers’ teaching methods have a strong correlation with students’ science performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the teacher level, it has been demonstrated that teacher shortage is negatively connected with students’ scientific literacy performance in many countries, such as in Brazil ( Kalkan et al, 2020 ), in Turkey and Singapore ( Alatli, 2020 ), and in Finland ( Nissinen et al, 2018 ). By studying PISA 2015 data, Ilgaz et al (2019) extended this negative relation to 70 countries. Furthermore, teachers’ teaching methods have a strong correlation with students’ science performance.…”
Section: Literature Reviewmentioning
confidence: 99%